Dynamical Analysis of Fractional-Order Hastings-Powell Food Chain Model with Alternative Food - Huda, Moh Nurul; Trisilowati, Trisilowati; Suryanto, Agus (The Journal of Experimental Life Science, 2017)
In this paper, a fractional-order Hastings-Powell food chain model is discussed. It is assumed that the top-predator population is supported by alternative food. Existence and local stability of equilibrium points of fractional-order system are investigated. Numerical simulations are conducted to illustrate analysis results. The analysis results show that alternative food can give a positive impact for top-predator population.Keywords: Alternative food, Fractional-order, Grunwald-Letnikov approximation, Hasting-Powell model, Stability.